2017
DOI: 10.1111/nrm.12130
|View full text |Cite
|
Sign up to set email alerts
|

Ecological modeling and eutrophication—A review

Abstract: During the several last decades, environmental scientists use numerical modeling as a tool in their studies and investigations of aquatic systems. Ecological and hydrodynamic models are developed in parallel regarding their complexity, uncertainty, and computational power. Ecological models have been used to assess ecosystem processes and interactions, simulate future scenarios, evaluate remedial practices in response to eutrophication etc. This review paper deals with the progress in ecological modeling relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 84 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…Several review papers focusing on mechanistic models have been published (e.g. Anagnostou et al, 2017;Arhonditsis and Brett, 2004).…”
Section: Mechanistic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several review papers focusing on mechanistic models have been published (e.g. Anagnostou et al, 2017;Arhonditsis and Brett, 2004).…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…They are therefore often coupled with a detailed hydrodynamic model and validated on field data. A comparison between nine complex dynamic models commonly used to study eutrophication can be found in (Anagnostou et al, 2017). Structurally dynamic models have then been proposed to add flexibility in the structure of the models (Jørgensen, 2015).…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…Aquatic ecological models describe the inherent mechanisms of change between individuals or populations in aquatic ecosystems, linking hydrology, water quality, meteorology, and other factors. They are mainly used to study eutrophication, biological enrichment, and food chains in aquatic systems [23]. Modern aquatic ecosystem models take into account the interaction between multiple factors in nature and spatiotemporal changes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many domestic studies have been conducted on this topic. For example, Wu et al used the EFDC model to predict the trends in chlorophyll and algal blooms and provided the criterion for the evaluation of algal bloom levels [23,24]. Dang et al developed a DELFT3D model and analyzed the impact of temperature, wind forcing, and nitrogen-phosphorus inputs on algal blooms, and they concluded that the simultaneous reduction in nitrogen and phosphorus is more effective in controlling algal growth [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these reviews were in the context of aquatic ecosystem models, applied not only to lakes and reservoirs, but also to rivers, estuaries, wetlands and oceans (e.g. Anagnostou et al, 2017;Brewer et al, 2018;Costa et al, 2019;De Goede, 2020;Robson 2014b), also including other modelling approaches, such as statistical and empirical models (e.g. Voinov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%